A Model of Multi-Cascade Fuzzy Logic Controller Implemented Using Different Variations of Inference Algorithms - Cherniy, S.P.; Buzikayeva, A.V.; Gudim, A.S. (2019 International Multi-Conference on Industrial Engineering and Modern Technologies (FarEastCon), 2019)
In the present work, the directions for expanding the intellectual capabilities of fuzzy control systems of complex technological objects are shown. Often, the operation of the control object is carried out either in the conditions of incomplete information, or significant deficiencies in the mathematical description, both in terms of the system of differential equations and in the restrictions imposed on the system as a whole. Overcoming these shortcomings with the use of typical fuzzy approaches is fraught with difficulties associated both with the algorithmic complexity of the knowledge base, the information redundancy of the linguistic variables used, and a significant number of fuzzy terms in a given control range. In the implementation of generally accepted control procedures based on soft calculations, difficulties arise with the implementation of the adaptive properties of such systems. The combination of various algorithms of fuzzy inference allows solving intellectual control problems for multicriteria and multifactor problems. At the same time, a different combination of such fuzzy conclusions enhances the various properties of such systems, for example, robustness, multitasking, aggregate control in the areas of large and small signals, etc. The paper presents models of two systems with a combination of algorithms for fuzzy logic inference Sugeno-Sugeno and Sugeno-Mamdani, analyzes the main characteristics of control systems using such multi-stage systems, identifies advantages and disadvantages for various combinations of algorithms, presents simulation results. In addition, some difficulties and features of setting up an external cascade, based on Sugeno's fuzzy logic inference algorithm, were identified, which can later be eliminated through the use of alternative output algorithms, for example, Mamdani. Features of the application of an algorithm in the internal cascade are most often dictated by the specifics of the operation of the control object, as well as by the criteria that can be imposed on it.